Plan de marketing para la importadora Ríos Cia. Ltda. de la ciudad de Machala - Zambrano Quevedo, Danitza Isabel (2015)
The marketing plan is a management tool by which the steps are determined, methodologies and timelines for achieving specific goals. Thus we have to PDMKT part of the strategic planning of a company. Thus, the Marketing Plan is a tool that allows us to set ourselves the way to reach a particular place. We can hardly produce it unless we know where we are and where we want to go. The basis of this research work is to analyze the process that is being implemented within the importing Rios. For the above is believed to pose a marketing plan for Rivers Importer of the city of Machala. The overall objective of this thesis is to establish marketing strategies for the company Importer Rivers city of Machala. Materials and methods were first used within the research used the historical method, which helped describe the facts and events that occurred in the importing company Rios, the scientific method allowed the diagnosis of the current situation, going through the company, which was the basis, both in theory and in practice during the investigation of this thesis, the inductive method was used to determine the results of the project, the same as were obtained through of the techniques applied, in order to be able to determine the various functions and activities performed by officers and employees of the company Importer Rios object of study, the deductive method, was used to analyze by the general data about the Strategic Plan Marketing for the company Importer Rivers, and suggest the proposal under consideration, the Descriptive Method, which allowed describe the current situation being experienced by the company under study, to conduct the study was learned the actual administrative business processes and their actions; within the technical allowed to apply a customer survey on a sample of 308 surveys, a survey of 17 employees and interview the Manager of the importing company Rios in these conditions the data they collaborated to develop the strengths, weaknesses, opportunities and threats, always relying on field research in the design of the SWOT matrix. After internal and external analyzes were performed by applying the EFE matrix, once the weighting assigned to each of the external factors influencing the importing Rivers, the weighted result of 2.67 was obtained, this means that in the importing rivers, there is a predominance of the opportunities we have. The IFE Matrix, once the weighting assigned to each of the internal factors that influence the importing Rivers, the weighted result of 2.52 was obtained, this means that in the importing Rivers, there is a predominance of strengths. With these considerations by High Impact Matrix, four objectives, among which are, Improved positioning of the company in the city of Machala at a cost of $ 4440.00 US dollars, implement strategic marketing plan were raised, in order to lead sales in the local market at a cost of $ 7700.00 US dollars, Develop an advertising plan in television and radio of the town to publicize the management of the company and the benefits of their products with a cost $ 6000 US dollars; and Conduct a staff training plan in order to improve business relationships, care and customer service, while improving the distribution of goods with a value of $ 650.00 US dollars, these targets given as costs by worth $ 18,790.00 US dollars. Among the most important findings is determined that the importing company Rios does not have a marketing plan, which improves the product to customers, so that strengthening is necessary and implement new strategies to address the weaknesses of the company. In the salient recommendations can be noted that the importer should apply Rivers strategic marketing plan developed to improve its market position in the province of El Oro